2000
DOI: 10.1128/mcb.20.15.5479-5489.2000
|View full text |Cite
|
Sign up to set email alerts
|

Increased Energy Expenditure, Decreased Adiposity, and Tissue-Specific Insulin Sensitivity in Protein-Tyrosine Phosphatase 1B-Deficient Mice

Abstract: Protein-tyrosine phosphatase 1B (PTP-1B) is a major protein-tyrosine phosphatase that has been implicated in the regulation of insulin action, as well as in other signal transduction pathways. To investigate the role of PTP-1B in vivo, we generated homozygotic PTP-1B-null mice by targeted gene disruption. PTP-1B-deficient mice have remarkably low adiposity and are protected from diet-induced obesity. Decreased adiposity is due to a marked reduction in fat cell mass without a decrease in adipocyte number. Leann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

66
989
5
8

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,156 publications
(1,068 citation statements)
references
References 75 publications
(76 reference statements)
66
989
5
8
Order By: Relevance
“…19,20,53 In this study, we show protection against the development of hepatic steatosis together with improved regenerative responses in PTP1B Ϫ/Ϫ mice fed an HFD before PH. In addition to the protection against insulin resistance and obesity, 20,54 an additional benefit of PTP1B deficiency may be the improvement of liver regeneration under conditions of increased lipid intake, as demonstrated herein by accelerated or increased induction of S-phase markers and an increased hepatosomal index compared with wild-type controls. In clinical situations, obese patients with fatty livers, who frequently develop insulin resistance, tend to have poor outcomes after resection or liver transplantation.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…19,20,53 In this study, we show protection against the development of hepatic steatosis together with improved regenerative responses in PTP1B Ϫ/Ϫ mice fed an HFD before PH. In addition to the protection against insulin resistance and obesity, 20,54 an additional benefit of PTP1B deficiency may be the improvement of liver regeneration under conditions of increased lipid intake, as demonstrated herein by accelerated or increased induction of S-phase markers and an increased hepatosomal index compared with wild-type controls. In clinical situations, obese patients with fatty livers, who frequently develop insulin resistance, tend to have poor outcomes after resection or liver transplantation.…”
Section: Discussionsupporting
confidence: 52%
“…18 Extensive analysis of the PTP1B-deficient (PTP1B Ϫ/Ϫ ) mice has confirmed that the IR is a key physiological target of PTP1B. 19,20 In fact, PTP1B inhibition is actually being assayed as a potential therapy for type 2 diabetes mellitus. Despite the negative modulation of activation of receptors of the tyrosine kinase superfamily by PTP1B, PTP1B Ϫ/Ϫ mice lack any obvious signs of increased activity of these receptors, such as susceptibility to tumor development through life.…”
mentioning
confidence: 99%
“…Total cell lysates were treated with the azide tagged PVSN probe (20 µM) for 30 min at room temperature and pH 6.0, and exposed to 0.125 mM of the alkyne-labeled biotin, 1.25 mM tris(2-carboxyethyl)phosphine (TCEP), 0.127 mM tris(benzyltriazolylmethyl)amine (TBTA), and 1.25 mM CuSO 4 for 1 hr to conjugate the PVSN-adducted HePTP with biotin for subsequent visualization. As shown in Figure 7, Western-blot analysis of the reaction mixture with anti-biotin and anti-(His) 6 antibodies showed robust labeling of HePTP, while little background labeling was observed for the entire non-PTP proteome under these conditions. This level of labeling specificity indicates that the PVSN/PVS scaffolds can be employed as activity-based probes to profile PTP activity in complex proteome.…”
Section: Specificity Of the Pvsn-based Probe In The Context Of A Compmentioning
confidence: 89%
“…With these reagents in hand, we assessed the compatibility of the PTP labeling strategy in a well-defined system, namely E. coli, which has no PTPs in its proteome. The specificity of the PVSN-based probe for targeted PTP analysis was evaluated in total cell lysates from both control E. coli and E. coli expressing recombinant (His) 6 -tagged HePTP. Total cell lysates were treated with the azide tagged PVSN probe (20 µM) for 30 min at room temperature and pH 6.0, and exposed to 0.125 mM of the alkyne-labeled biotin, 1.25 mM tris(2-carboxyethyl)phosphine (TCEP), 0.127 mM tris(benzyltriazolylmethyl)amine (TBTA), and 1.25 mM CuSO 4 for 1 hr to conjugate the PVSN-adducted HePTP with biotin for subsequent visualization.…”
Section: Specificity Of the Pvsn-based Probe In The Context Of A Compmentioning
confidence: 99%
See 1 more Smart Citation